COMPARISON OF CYCLIC FATIGUE RESISTANCE OF ONE CURVE, HYFLEX EDM, WAVEONE GOLD AND RECIPROC BLUE NICKELTITANIUM ROTARY FILES AT INTRA-CANAL TEMPERATURE - Koray Yılmaz; Taha Özyürek; Gülşah Uslu (Cumhuriyet University, 2019)
Objectives: To compare the cyclic fatigue resistances of One Curve (OC), Hyflex EDM (HEDM), WaveOne Gold (WOG), Reciproc Blue (RPC Blue), and nickel-titanium rotary files at intra-canal temperature (35°C). Materials and Methods: Twenty OC (25/.06), 20 HEDM (25/.08), 20 WOG (25/.07) and 20 RPC Blue (25/.08) files were tested for cyclic fatigue at intra-canal temperature (35°C). All the instruments were rotated in artificial which were made of stainless steel with an 60° angle of curvature and a radii of curvatures of 5 mm until fracture occurred, and the time to fracture was recorded in seconds using a digital chronometer and the number of cycles to fracture (NCF) for each file was calculated. The Kruskal-Wallis test was performed to statistically analyze the data by using SPSS 21.0 software. The statistical significance level was set at p<.05.Results: NCF values revealed that the HEDM had the highest cyclic fatigue resistance at intracanal temperature (p<.05) and followed by WOG, RPC Blue and OC. The lowest NCF values were determined in the OC group and statistically significant difference was observed between the OC group the other groups (p<.05). No statistically significant difference in the mean length of the fractured fragments in curvature was evident for the instruments (p> .05).Conclusion: Within the limitations of the present in-vitro study, HEDM instrument resisted static cyclic fatigue significantly more than RPC Blue, WOG and OC instruments.